Formulation of new drug delivery system containing anti-microbial agent for treatment of periodontal diseases - Yara Essam Ahmed Mohamed; Amna Mohammed Makky; Doaa Ahmed Elsetouhy (Cairo : Yara Essam Ahmed Mohamed, 2016)
Periodontal diseases are a general term which encompasses several pathological conditions affecting the tooth supporting structures. These conditions are characterized by a destruction of the periodontal ligament, a resorbtion of the alveolar bone and the migration of the junctional epithelium along the tooth surface. The clinical signs of periodontitis are changes in the morphology of gingival tissues, bleeding upon probing as well as periodontal pocket formation. This pocket provides an ideal environment for the growth and proliferation of anaerobic pathogenic bacteria. The microorganisms colonizing the subgingival area represent the principal etiological factor in the development of the inflammation and tissue destruction
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Pharmaceutics
Issued also as CD
Keywords: Doxycycline Hyclate; Eugenol; Treatment of periodontal diseases